Speciic Features of Managing Interaction of Business and Higher Education - Yu. V. Kotelevskaya (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies factors affecting the efficiency of interaction between small business and higher education, tools of interaction between business and higher education and identifies problems of non-coordination of business and higher education. The necessity to upgrade infrastructural support of business and higher education interaction was substantiated. The current practices of business and higher education were investigated, which gave an opportunity to come to the conclusion about inefficiency of these ties. Misbalance of labour market, absence of demand for graduates of higher education on regional market and consequently, outflow of young highly-qualified workers show the need to upgrade ways of interaction between business and higher education and to develop the adequate infrastructure. The author grounds the necessity to raise professional competences of business in order to build foundation for the development of innovative forms of entrepreneurship and involvement of young qualified personnel with higher education in their work. Analysis of business and education interaction allows us to improve efficiency of interaction between business and higher education by setting-up the education cluster. Within the frames of the education cluster creating investment appeal of higher education is created.